A dinâmica da expansão urbana no município de São Paulo: os impactos do Rodoanel Mário Covas para o distrito de Perus - Debonis, Marcelo (2011)
The objective of this dissertation is to reflect about the socio-environmental impacts in areas where big size infrastructure roadworks have been developed, specially those of highway mode, taking as example the district of Perus in the city of São Paulo where in the year of 2002, it was released for the traffic the west stretch of betway Mário Covas. There were selected for this study the environmental, social and political impacts generated in the region as a whole and specifically in the district. The research focused the comprehension of the complex relationships inherent in the set up and consolidation of the interests represented by several parts involved, i.e., the government, the premises of private enterprises and the ambition of the citizens living in this location. It was made a hystorical survey of the district occupancy and of the development of the roadworks. Taking as theoretical reference the context of mondialization, the ideology of global cities and the culture of road transport in Brazil, there were investigated the peculiarities of the implementation process of the beltway in the region, the role represented by governmet and by private enterprises during the process and the most significant metamorphoses verified in the scope of Perus district. More accurately, the intention was to investigate the consequences of the new reality represented by the construction of the beltway, the contradictions that were established throughout the process and the eventual repercussions for the district